Design of microirrigation systems in sloping lands using linear programming - Saad, João Carlos Cury [UNESP]; Mariño, Miguel A. (My University, 2000)
When the area to be irrigated has a high slope gradient in the manifold line direction, an option is to use a tapered pipeline to economize on pipe costs and to keep the pressure head variations within desired limits. The purpose of this paper is to develop a linear programming model to design a microirrigation system with tapered manifold lines in the downhill condition, minimizing the equivalent annual cost of the hydraulic network and the energy annual cost, and assuring that the maximum variation in the pressure head previously established will be observed. The input data are: irrigation system lay-out, cost of all hydraulic network components and energy cost. The output are: equivalent annual cost, pipeline diameter in each line of the system, pressure head in each node, and total operating pressure head. To illustrate its capability, the model is applied in a citrus orchard in Sao Paulo State, Brazil. The model proved to be efficient in the design of the irrigation system in terms of the emission uniformity desired. The annual pumping cost must be considered in the microirrigation system design because it yields a lower total annual cost when compared with the same alternative without that cost.
Keywords: Linear programming; Microirrigation; Optimization; Slope land; Costs; Mathematical models; Pressure effects; Slope protection; Energy costs; Hydraulic networks; Irrigation